ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN POWER POINT DALAM PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - Krisanta Simarmata; Rahmatika Elindra; Eva Yanti Siregar (JURNAL MathEdu (Mathematic Education Journal), 2021)
The background of the research is the Covid - 19 pandemic that hit all countries in parts of the world, including Indonesia. This problem creates a home learning program policy by implementing online learning. The purpose of this study was to describe the use of power points in online learning during the Covid-19 pandemic at the eleventh grade students of SMA Negeri 1 Andam Dewi.The approach of the research used qualitative descriptive by applying data analysis technique which includes data reduction, presentation, and taking conclusion. Questionnaire and interview were used in collecting the data with 15 students as the respondents. The result of the research shows 4 students are decent, 7 students are enough decent, and 4 students are less decent. It’s concluded that the average of using power point is 35.26% (enough decent).